High-temperature-resistant low-loss radio frequency cable for intelligent networked automobile and preparation process thereof

By using a specific ratio of phosphorus-based compounds to modify magnesium-aluminum hydrotalcite, zinc borate and lanthanum modified St-MAH-AN terpolymers in the sheath layer of the radio frequency cable for intelligent connected vehicles, the problem of cable aging, cracking or melting of wireless charging and discharge systems at high temperatures is solved, efficient thermal stability and mechanical strength improvement are achieved, and the safety of the system is ensured.

CN119842170AActive Publication Date: 2025-04-18JIANGSU ELESUN CABLE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510338811.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

New energy vehicle wireless charging and discharging systems generate a large amount of heat during high power charging, resulting in the existing low-loss RF cables being easily aged, cracked or melted at high temperatures, and there are safety hazards such as short circuits and leakage.

Method used

A high-temperature and low-loss radio frequency cable for intelligent connected vehicles is adopted. The sheath layer is composed of polyvinyl chloride, phosphorus-based compound modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum modified St-MAH-AN terpolymer. Through specific ratios and process treatment, the thermal stability and mechanical strength of the sheath layer are improved.

Benefits of technology

It significantly improves the high temperature resistance of the cable, ensures that it does not fuse at the maximum fire supply temperature above 850℃, reduces the probability of safety hazards such as short circuit and leakage, and ensures the safe operation of the charging and discharging system and the safety of users.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842170A_ABST
    Figure CN119842170A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses a high-temperature-resistant low-loss radio frequency cable for an intelligent networked automobile and a preparation technology thereof.The high-temperature-resistant low-loss radio frequency cable for the intelligent networked automobile comprises a sheath layer, and the sheath layer is prepared from, by weight, 100 parts of polyvinyl chloride; 30 to 35 parts of an acrylate copolymer; 15-20 parts of a heat stabilizer and 15-20 parts of a fire-resistant filler; the intrinsic viscosity of the acrylate copolymer is less than 5.8 dL / g, and the heat stabilizer comprises phosphorus compound modified magnesium-aluminum hydrotalcite, zinc borate and a lanthanum modified St-MAH-AN terpolymer in a weight ratio of 25: 5: (5-8). The high-temperature-resistant low-loss radio frequency cable has the highest fire supply temperature of 850 DEG C or above, and the possibility of aging, cracking or melting of the sheath layer at the high temperature is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer materials, and in particular to a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles and a preparation process thereof. Background Art

[0002] The wireless charging and discharging system for new energy vehicles is a system that uses the principle of electromagnetic induction or magnetic resonance to transmit electrical energy between the transmitting coil of the charging station and the receiving coil on the electric vehicle. It can charge or discharge electric vehicles without physical contact, and is currently a very advanced technology. The system consists of a transmitting end (usually installed at a charging station or parking space, containing a transmitting coil and a control circuit), a receiving end (installed on the electric vehicle, containing a receiving coil and a rectifier circuit, used to convert the received AC power into DC power for battery charging), and a radio frequency cable (a cable that transmits electromagnetic energy in the radio frequency range) used to connect the transmitting end and the receiving end. The system generates current in the receiving coil through a changing magnetic field, and uses the same resonant frequency of the two coils to achieve efficient wireless transmission of electrical energy.

[0003] Since the wireless charging and discharging system does not require physical plugging and unplugging, it can greatly improve the convenience of charging and user experience. At the same time, it avoids the risk of electric sparks and electric shock caused by contact charging. Therefore, it is very suitable for use in severe weather conditions and has a high safety factor. However, although this system has many advantages, it also has many problems that need to be solved. There is energy loss in the wireless transmission process, and technicians need to optimize the system design, such as using low-loss RF cables to improve transmission efficiency. However, with the development of low-loss RF cables, people have discovered a more difficult problem, that is, the wireless charging and discharging system will generate a lot of heat when charging at high power. The existing low-loss RF cables are prone to aging, cracking or melting of the sheath layer at high temperatures, and the possibility of safety hazards such as short circuits and leakage is very high. This requires the cable, a key connection component, to have good high temperature resistance to ensure system stability and safety. Therefore, in order to ensure the safe operation of the charging and discharging system and the personal safety of users, how to improve the high temperature resistance of low-loss RF cables used in wireless charging and discharging systems for new energy vehicles has become a current research hotspot. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a high temperature resistant and low loss radio frequency cable for intelligent connected vehicles and a preparation process thereof.

[0005] In the first aspect, the present application provides a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles, comprising a twisted core, a winding layer, a shielding layer and a sheath layer sequentially coated on the outside of the twisted core, wherein the raw materials used for the sheath layer include the following components by weight: 100 parts of polyvinyl chloride; 30-35 parts of acrylic copolymer; 15-20 parts of thermal stabilizer and 15-20 parts of refractory filler; the intrinsic viscosity of the acrylic copolymer is less than 5.8 dL / g, and the thermal stabilizer includes a phosphorus-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN ternary copolymer in a weight ratio of 25:5:(5-8).

[0006] Preferably, the raw materials used for the sheath layer include the following components in parts by weight: 100 parts of polyvinyl chloride; 32 parts of acrylic copolymer; 18 parts of heat stabilizer and 18 parts of refractory filler.

[0007] Optionally, the refractory filler includes at least two of mica, calcium carbonate, magnesium oxide and antimony trioxide.

[0008] By adopting the above technical scheme, the present application utilizes a heat stabilizer obtained by mixing a phosphorus-modified magnesium-aluminum hydrotalcite, zinc borate and a lanthanum-modified St-MAH-AN ternary copolymer and a refractory filler to work together to improve the thermal stability of the sheath layer, wherein the phosphorus-modified magnesium-aluminum hydrotalcite contains a variety of phosphorus-modified compounds, and the layered structure of the magnesium-aluminum hydrotalcite can play a hydrogen bond and electrostatic attraction role. When heated, the layer hydroxyl groups and the anions between the layers and the structural water will escape, reducing the ambient oxygen concentration and the ambient temperature. Therefore, the phosphorus-modified magnesium-aluminum hydrotalcite has good flame retardancy and heat resistance; zinc borate has a flame retardant mechanism and excellent heat resistance similar to those of phosphorus compounds, and also has a synergistic ability far exceeding other heat stabilizers, which can optimize the effects of other blended heat stabilizers, and the lanthanum-modified St-MAH-AN ternary copolymer has the characteristics of non-toxicity, environmental protection and excellent thermal stability. After the three are blended, they can give full play to the good synergistic effect and greatly improve the thermal stability of the sheath layer. At the same time, the present application also adds an acrylic copolymer to improve the compatibility of various substances in the system, and controls its intrinsic viscosity to be less than 5.8 dL / g. The acrylic copolymer with the intrinsic viscosity is dispersed in the system, which can effectively entangle with the molecular chain of polyvinyl chloride, ensuring that the refractory filler and the thermal stabilizer are fully interspersed in the polyvinyl chloride matrix, so that the internal compatibility of the sheath layer is significantly optimized, thereby simultaneously improving the thermal stability and mechanical stability of the sheath layer.

[0009] In summary, the present application makes full use of the thermal stabilizer and refractory filler to improve the thermal stability of the sheath layer, and uses the acrylic copolymer with a characteristic viscosity of less than 5.8 dL / g to improve the compatibility between the substances in the system. The above substances are blended and extruded with polyvinyl chloride to obtain a sheath layer with good thermal stability and mechanical strength, which plays a good protective role on the cable as a whole. Therefore, the high temperature resistant and low loss RF cable for intelligent networked vehicles of the present application has a maximum fire supply temperature of more than 850°C (the maximum temperature at which the 2A fuse does not melt and the conductor does not melt) and a friction (50N friction force) mass loss rate of less than 1.5%, and the mass retention rate at a temperature of 150°C is not less than 97.5%, which greatly reduces the possibility of aging, cracking or melting of the sheath layer at high temperature, and also reduces the possibility of safety hazards such as short circuit and leakage to almost zero, which fully guarantees the safe operation of the charging and discharging system and the personal safety of the user, and has a high use value.

[0010] Preferably, the heat stabilizer comprises a phosphorus-based compound-modified magnesium-aluminum hydrotalcite, zinc borate and a lanthanum-modified St-MAH-AN terpolymer in a weight ratio of 25:5:7.5.

[0011] By adopting the above technical scheme, the weight ratio of phosphorus-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN ternary copolymer in the thermal stabilizer is strictly controlled to 25:5:7.5. This specific ratio can maximize the synergistic effect of each component. Specifically, phosphorus-modified magnesium-aluminum hydrotalcite has good flame retardant and heat-resistant properties, can decompose and absorb heat at high temperature, and reduce oxygen concentration; zinc borate further enhances the flame retardant effect, while optimizing the effects of other thermal stabilizers; lanthanum-modified St-MAH-AN ternary copolymer improves the mechanical strength and weather resistance of the material. The composite effect of these components at the optimal ratio significantly improves the overall thermal stability and mechanical properties of the sheath layer, effectively prevents aging, cracking or melting of the insulating layer at high temperature, thereby reducing the probability of safety hazards such as short circuit and leakage, and ensuring the safe and reliable operation of the charging and discharging system. Experimental data show that the maximum fire supply temperature of the high-temperature resistant and low-loss RF cable for intelligent connected vehicles is significantly improved at this time.

[0012] Preferably, the acrylic copolymer is prepared by the following method: methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan in a weight ratio of 120:10:(0.5-2.0) are mixed and dispersed in water containing initiator a and emulsifier, stirred for reaction, demulsified, and dried to obtain an acrylic copolymer with an intrinsic viscosity of less than 5.8 dL / g.

[0013] By adopting the above technical scheme, the present application uses a certain proportion of methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan to blend, wherein tert-dodecyl mercaptan plays the role of a chain transfer agent, and reacts in an aqueous medium containing initiator a and an emulsifier. The resulting acrylic copolymer has a low intrinsic viscosity (<5.8 dL / g), which not only improves the compatibility of various substances in the sheath layer, but also further enhances the mechanical stability and thermal stability of the sheath layer, thereby effectively improving the overall high temperature resistance of the cable, reducing the risk of aging, cracking or melting of the sheath layer under high temperature conditions, and ensuring the safe and reliable operation of the charging and discharging system. Compared with acrylic monomers such as butyl acrylate, methyl acrylate and isooctyl acrylate, the isobornyl acrylate of the present application has better thermal stability, durability, lower viscosity and toxicity, and has both good performance and environmental protection characteristics. After adding it to the acrylic copolymer, it can further improve the compatibility inside the sheath layer, thereby improving the overall thermal stability and mechanical stability of the cable. In the present application, the initiator a is potassium persulfate and the emulsifier is sodium dodecyl sulfate. Those skilled in the art can reasonably replace the above two substances according to actual conditions. Therefore, the specific selection of initiator a and emulsifier in the embodiments of the present application cannot limit the protection scope of the present application.

[0014] Preferably, the weight ratio of methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan is 120:10:1.3.

[0015] By adopting the above technical solution, the present application strictly controls the weight ratio of methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan, so that the characteristic viscosity of the acrylate copolymer is at the most suitable size, further improving the compatibility of various substances in the sheath layer and the overall mechanical strength and thermal stability of the sheath layer. If the amount of tert-dodecyl mercaptan is too large, the conversion rate of methyl methacrylate will be greatly reduced (cannot reach more than 98%), resulting in too many methyl methacrylate and isobornyl acrylate monomers in the system, which cannot effectively improve the compatibility of the system; if the amount of tert-dodecyl mercaptan is too small, the characteristic viscosity of the acrylate copolymer will rise sharply, which also cannot effectively improve the compatibility of the system. Experimental data show that when the weight ratio of the three is controlled at 120:10:1.3 in the present application, the maximum fire supply temperature of the high temperature resistant and low loss RF cable for intelligent connected vehicles will be significantly improved, and the mass loss rate will also be reduced.

[0016] Preferably, the phosphorus compound in the phosphorus compound-modified magnesium-aluminum hydrotalcite includes ammonium polyphosphate, resorcinol bis(diphenyl phosphate) and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in a weight ratio of 1:(0.5-1):(1-1.5).

[0017] By adopting the above technical scheme, the present application utilizes ammonium polyphosphate, resorcinol bis(diphenyl phosphate) and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to blend and modify the magnesium-aluminum hydrotalcite, and strictly controls the weight ratio of the three, so that the phosphorus-based compound-modified magnesium-aluminum hydrotalcite can form a stable protective film in the sheath layer system when the cable is heated, effectively inhibiting the decomposition and combustion of the sheath layer, reducing smoke generation, and improving the overall flame retardant performance and heat stability of the sheath layer. Specifically, ammonium polyphosphate, as the main carbonizing agent, promotes carbonization at high temperatures, enhances the thermal insulation and oxygen isolation of the carbon layer; resorcinol bis(diphenyl phosphate) has excellent antioxidant properties, delaying the aging process of the material; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide further improves the thermal stability and flame retardant effect of the material, and the three work synergistically to significantly improve the comprehensive protective performance of the sheath layer under high temperature conditions.

[0018] Preferably, the lanthanum-modified St-MAH-AN terpolymer is prepared by the following method: styrene, acrylonitrile, maleic anhydride and initiator b are blended, heated to react, washed, dried to obtain a terpolymer, and then the terpolymer is dispersed in an alkaline solution, heated and stirred until the system is completely clarified and then kept warm, and then a lanthanum chloride solution is added to ensure that the weight ratio of the terpolymer to the lanthanum ion in the system is 10: (0.5-1), stirred to react, cooled, allowed to stand, filtered to obtain a filter residue, washed, and dried to obtain a lanthanum-modified St-MAH-AN terpolymer. The initiator b in this application is dibenzoyl peroxide, and those skilled in the art can reasonably replace the above substances according to actual conditions, so the specific selection of the initiator b in the embodiment of this application cannot limit the scope of protection of this application.

[0019] By adopting the above technical scheme, the present application first generates a ternary copolymer of styrene, acrylonitrile and maleic anhydride, and then introduces lanthanum ions through its reaction with lanthanum chloride to form a lanthanum-modified St-MAH-AN ternary copolymer with excellent thermal stability. The substance has excellent compatibility with polyvinyl chloride and good processing and molding properties. At the same time, the internal anhydride group also has good derivatization ability, and the cyano group can provide high hardness and low friction coefficient. Therefore, the lanthanum-modified St-MAH-AN ternary copolymer of the present application significantly enhances the overall thermal stability and mechanical strength of the sheath layer. This helps to prevent aging, cracking or melting of the cable insulation layer in a high temperature environment, effectively reduces the probability of safety hazards such as short circuits and leakage, greatly improves the wear resistance of the cable, further ensures the appearance integrity of the cable, and ensures the safe operation of the wireless charging and discharging system of new energy vehicles and the personal safety of users.

[0020] Preferably, after adding the lanthanum chloride solution, the weight ratio of the terpolymer to the lanthanum ions in the system is 10:0.8.

[0021] By adopting the above technical scheme, the present application strictly controls the weight ratio of the terpolymer to lanthanum ions, optimizes the lanthanum doping rate to the greatest extent without incurring additional costs, and maximizes the heat resistance of the sheath layer. It effectively prevents aging, cracking or melting of the sheath layer caused by high temperature, reduces the risk of short circuit and leakage, and ensures the safe and reliable operation of the cable.

[0022] In a second aspect, the present application provides a preparation process of a high temperature resistant and low loss radio frequency cable for an intelligent connected vehicle, comprising the following steps: S1, mixing: the polyvinyl chloride, heat stabilizer and refractory filler are stirred at a speed of 800-1000 r / min, and then the acrylic copolymer is added at a speed of 600-800 r / min, and after the addition is completed, the material is mixed at a speed of 1200-1400 r / min until there is no powder accumulation on the liquid surface, and then the material is further mixed at a speed of 1200-1400 r / min to obtain a mixture; S2. Preparing a crude cable: coating an insulating layer on the surface of a conductor to obtain a twisted wire core, and then sequentially coating a sheath layer and a shielding layer on the outer side of the twisted wire core to obtain a crude cable; S3. Preparation of high temperature resistant and low loss radio frequency cable: Extruding the mixture obtained in step S1 onto the outside of the crude cable obtained in step S2 to form a sheath layer, thereby obtaining a high temperature resistant and low loss radio frequency cable.

[0023] By adopting the above technical solution, the preparation process of the high temperature resistant and low loss RF cable for intelligent connected vehicles provided by this application can effectively improve the thermal stability and mechanical strength of the sheath layer. Specifically, by uniformly stirring polyvinyl chloride, heat stabilizer and refractory filler at a specific speed, and then gradually adding acrylic copolymers, the raw materials used for the sheath finally obtained have excellent thermal stability and compatibility, and can maintain good physical properties in a high temperature environment, and prevent the occurrence of aging, cracking or melting of the sheath layer caused by high temperature, thereby significantly reducing safety hazards such as short circuit and leakage. In addition, the preparation process also ensures the twisting quality of the conductor and the close fit of the insulation layer, the sheath layer and the shielding layer, further improving the overall performance and reliability of the cable.

[0024] The raw material used for the conductor of the present application is tinned copper wire with a cross-sectional area of ​​0.16±0.01mm² (the cross-sectional area and material improve the current-carrying capacity of the conductor and reduce the resistance value, which means lower energy loss, which is particularly important in the process of large current transmission, and the tin plating treatment effectively enhances the oxidation resistance and corrosion resistance of the copper wire, further extends the service life of the conductor, and ensures the reliability and stability of long-term use), the raw material used for the insulating layer is foamed polypropylene, the raw material used for the winding layer is double-sided non-self-adhesive aluminum foil, and the raw material used for the shielding layer is a braided tinned copper wire with a specification of 16×6×0.10±0.01mm. Those skilled in the art can reasonably replace the above substances according to actual conditions. Therefore, the specific selection of the raw materials used for the insulating layer, the winding layer and the shielding layer in the embodiment of the present application cannot limit the protection scope of the present application.

[0025] In summary, this application has the following beneficial technical effects: 1. The present application uses a phosphorus compound modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum modified St-MAH-AN terpolymer with a specific ratio as a thermal stabilizer, which significantly improves the high temperature resistance of the sheath layer, so that it can remain unmelted at the highest fire supply temperature above 850°C, effectively preventing the sheath layer of the cable from aging, cracking or melting in a high temperature environment, and reducing the risk of short circuit and leakage; 2. This application enhances the compatibility and mechanical stability between various substances inside the sheath layer by adding an acrylic copolymer and controlling its intrinsic viscosity to be less than 5.8 dL / g, thereby further improving the overall durability and reliability of the cable; 3. The sheath layer of the present application has excellent thermal stability and mechanical strength, which ensures the stability and safety of the cable during high-power charging, and fully guarantees the normal operation of the wireless charging and discharging system and the safety of users. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a cross-sectional view of the high temperature resistant and low loss radio frequency cable for the intelligent connected vehicle of the present application. DETAILED DESCRIPTION

[0027] The following is combined with Figure 1 The cable structure of the present application is further described in detail.

[0028] like Figure 1As shown, the conductor is twisted by seven tinned copper wires with a cross-sectional area of ​​0.16±0.01mm², with an overall outer diameter of 0.48mm. Foamed polypropylene is extruded on the outside of the conductor to form a tightly wrapped insulating layer. After the insulating layer is coated, the overall outer diameter is 1.25±0.05mm. The conductor and the insulating layer form a twisted core. Each cable contains two sets of identical twisted cores, which are twisted into a cable in a right-hand back-twisting manner at a twisting pitch of 20±2mm. The outer sides of the two sets of twisted cores after twisting are coated with double-sided non-self-adhesive aluminum foil to form a sheath, so that the overall outer diameter reaches 2.60±0.1mm. The outer side of the sheath is then coated with a braided tinned copper wire with a specification of 16×6×0.10±0.01mm to form a shielding layer, so that the overall outer diameter reaches 2.70±0.1mm, forming a coarse cable.

[0029] In order to further verify the relevant performance of the sheath layer of the present application, the applicant uses the following examples and comparative examples for detailed description.

[0030] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Methyl methacrylate was purchased from Jilin Chemical Industry Company; Isobornyl acrylate was purchased from Jilin Chemical Industry Company; Butyl acrylate was purchased from Jilin Chemical Industry Company; Methyl acrylate was purchased from Jilin Chemical Industry Company; Isooctyl acrylate was purchased from Jilin Chemical Industry Company; Tert-dodecyl mercaptan was purchased from Shandong Yukang Chemical Co., Ltd.; Magnesium-aluminum hydrotalcite was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ammonium polyphosphate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Resorcinol bis(diphenyl phosphate) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No. 57583-54-7; 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No. 35948-25-5; Bisphenol A-bis(diphenyl phosphate) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No. 5945-33-5; Ammonium dihydrogen phosphate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Polyvinyl chloride was purchased from Hanwha Chemical (Ningbo) Co., Ltd.; Zinc borate was purchased from Shandong Jiuchong Chemical Co., Ltd.; Mica was purchased from Shandong Yuanbang New Materials Co., Ltd.; Antimony trioxide was purchased from Shandong Yuanbang New Materials Co., Ltd.; Magnesium oxide was purchased from Shandong Yuanbang New Materials Co., Ltd.; Calcium carbonate was purchased from Shandong Yuanbang New Materials Co., Ltd.; Dioctyl phthalate was purchased from Shandong Jichuang Chemical Co., Ltd.

[0031] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0032] Method for testing the intrinsic viscosity: Place the acrylic copolymer in a constant temperature box at 65°C for 10 hours. After cooling, use a precision balance to accurately weigh 0.75g of the sample and transfer it to a 250ml volumetric flask. Subsequently, add 150mL of chloroform to the volumetric flask and place it in a constant temperature water bath at (35±0.1)°C for 12 hours to allow the sample to completely dissolve. After the dissolution is complete, dilute the solution to 250ml with chloroform. Finally, use an Ubbelohde viscometer to measure the viscosity of the solution and chloroform, respectively. The formula for calculating the intrinsic viscosity is as follows: η r = t / t0; η sp =η r -1; η=1 / c*(η sp -ln η r ) -2 ; t: time for the modifier solution to flow through the capillary / s, t0: time for the solvent chloroform to flow through the same capillary / s, c: mass concentration of the solution / g per 100mL, η r : Relative viscosity, η sp : specific viscosity, η: intrinsic viscosity.

[0033] Preparation Example 1.1 The preparation method of the acrylic acid ester copolymer comprises the following steps: 0.8 kg of potassium persulfate and 4 kg of sodium dodecyl sulfate were dispersed in 200 L of water, and nitrogen was introduced for protection. Stirring was continued at 60 ° C for 5 min, and then 12 kg of methyl methacrylate, 1 kg of isobornyl acrylate and 50 g of tert-dodecyl mercaptan were added. The reaction was kept warm for 6 h at a stirring rate of 230 r / min. The conversion rate of methyl methacrylate was detected. When it reached 98%, the material was taken out for demulsification and drying to obtain an acrylic copolymer with an intrinsic viscosity of 5.78 dL / g.

[0034] Preparation Example 1.2 The preparation method of the acrylic acid ester copolymer comprises the following steps: 0.8 kg of potassium persulfate and 4 kg of sodium dodecyl sulfate were dispersed in 200 L of water, and nitrogen was introduced for protection. Stirring was continued at 60 ° C for 5 min, and then 12 kg of methyl methacrylate, 1 kg of isobornyl acrylate and 200 g of tert-dodecyl mercaptan were added. The reaction was kept warm for 6 h at a stirring rate of 230 r / min. The conversion rate of methyl methacrylate was detected. When it reached 98%, the material was taken out for demulsification and drying to obtain an acrylic copolymer with an intrinsic viscosity of 1.03 dL / g.

[0035] Preparation Example 2.1 The preparation method of the acrylic ester copolymer is different from that of Preparation Example 1.1 in that the amount of tert-dodecyl mercaptan used is 90 g, and the rest is the same as Preparation Example 1.1, and an acrylic ester copolymer with an intrinsic viscosity of 4.86 dL / g is obtained.

[0036] Preparation Example 2.2 The preparation method of the acrylic copolymer is different from that of Preparation Example 1.1 in that the amount of tert-dodecyl mercaptan used is 130 g, and the rest is the same as Preparation Example 1.1, and an acrylic copolymer with an intrinsic viscosity of 3.24 dL / g is obtained.

[0037] Preparation Example 2.3 The preparation method of the acrylic ester copolymer is different from that of Preparation Example 1.1 in that the amount of tert-dodecyl mercaptan used is 170 g, and the rest is the same as Preparation Example 1.1, and an acrylic ester copolymer with an intrinsic viscosity of 2.19 dL / g is obtained.

[0038] Preparation Example 3.1 The preparation method of the acrylic acid ester copolymer is different from that of Preparation Example 2.2 in that isobornyl acrylate is replaced by butyl acrylate, and the rest is the same as Preparation Example 2.2, and an acrylic acid ester copolymer with an intrinsic viscosity of 4.10 dL / g is obtained.

[0039] Preparation Example 3.2 The preparation method of the acrylic acid ester copolymer is different from that of Preparation Example 2.2 in that isobornyl acrylate is replaced by methyl acrylate, and the rest is the same as Preparation Example 2.2, and an acrylic acid ester copolymer with an intrinsic viscosity of 3.86 dL / g is obtained.

[0040] Preparation Example 3.3 The preparation method of the acrylic acid ester copolymer is different from that of Preparation Example 2.2 in that isobornyl acrylate is replaced by isooctyl acrylate, and the rest is the same as Preparation Example 2.2, and an acrylic acid ester copolymer with an intrinsic viscosity of 4.02 dL / g is obtained.

[0041] Preparation Example 4.1 The preparation method of phosphorus compound modified magnesium aluminum type hydrotalcite comprises the following steps: A total of 6 kg of phosphorus compounds were continuously stirred at a temperature of 120° C. until they were completely melted, and then 1.2 kg of magnesium-aluminum hydrotalcite was added. After stirring for 6 hours, stirring was stopped, and the solid matter was filtered, washed, and then placed in a drying oven, dried at 60° C. for 30 minutes, and ground to 500 mesh after drying to obtain phosphorus-compound-modified magnesium-aluminum hydrotalcite, wherein the phosphorus compound was obtained by mixing 2 kg of ammonium polyphosphate, 1 kg of resorcinol bis(diphenyl phosphate) and 3 kg of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0042] Preparation Example 4.2 The preparation method of phosphorus compound modified magnesium aluminum type hydrotalcite comprises the following steps: A total of 6 kg of phosphorus compounds were continuously stirred at a temperature of 120° C. until they were completely melted, and then 1.2 kg of magnesium-aluminum hydrotalcite was added. After stirring for 6 hours, stirring was stopped, and the solid matter was filtered, washed, and then placed in a drying oven, dried at 60° C. for 30 minutes, and ground to 500 mesh after drying to obtain phosphorus-compound-modified magnesium-aluminum hydrotalcite, wherein the phosphorus compound was obtained by mixing 2 kg of ammonium polyphosphate, 2 kg of resorcinol bis(diphenyl phosphate) and 2 kg of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0043] Preparation Example 4.3 The preparation method of phosphorus compound modified magnesium aluminum type hydrotalcite comprises the following steps: A total of 6 kg of phosphorus compounds were continuously stirred at a temperature of 120° C. until they were completely melted, and then 1.2 kg of magnesium-aluminum hydrotalcite was added. After stirring for 6 hours, stirring was stopped, and the solid matter was filtered, washed, and then placed in a drying oven, dried at 60° C. for 30 minutes, and ground to 500 mesh after drying to obtain phosphorus-compound-modified magnesium-aluminum hydrotalcite, wherein the phosphorus compound was obtained by mixing 2 kg of ammonium polyphosphate, 0.5 kg of resorcinol bis(diphenyl phosphate) and 3.5 kg of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0044] Preparation Example 4.4 The preparation method of phosphorus compound modified magnesium aluminum type hydrotalcite comprises the following steps: A total of 6 kg of phosphorus compounds were continuously stirred at a temperature of 120° C. until they were completely melted, and then 1.2 kg of magnesium-aluminum hydrotalcite was added. After stirring for 6 hours, stirring was stopped, and the solid matter was filtered, washed, and then placed in a drying oven, dried at 60° C. for 30 minutes, and ground to 500 mesh after drying to obtain phosphorus-compound-modified magnesium-aluminum hydrotalcite, wherein the phosphorus compound was obtained by mixing 2 kg of ammonium polyphosphate, 3.5 kg of resorcinol bis(diphenyl phosphate) and 0.5 kg of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0045] Preparation Example 5.1 The preparation method of phosphorus-based compound-modified magnesium-aluminum hydrotalcite is different from that of Preparation Example 4.1 in that resorcinol bis(diphenyl phosphate) is replaced by triphenyl phosphate, and the rest is the same as that of Preparation Example 4.1.

[0046] Preparation Example 5.2 The preparation method of phosphorus-modified magnesium-aluminum hydrotalcite is different from that of Preparation Example 4.1 in that 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is replaced by bisphenol A-bis(diphenyl phosphate), and the rest is the same as Preparation Example 4.1.

[0047] Preparation Example 5.3 The preparation method of phosphorus-compound-modified magnesium-aluminum hydrotalcite is different from that of Preparation Example 4.1 in that ammonium polyphosphate is replaced by diammonium dihydrogen phosphate, and the rest is the same as that of Preparation Example 4.1.

[0048] Preparation Example 6.1 The preparation method of lanthanum modified St-MAH-AN terpolymer comprises the following steps: 3kg of styrene, 2kg of acrylonitrile, 8kg of maleic anhydride and 30g of dibenzoyl peroxide were mixed and reacted at 70°C for 2h. At this time, the polymerization liquid became viscous. It was washed with a 3wt% ethanol solution and dried to obtain a terpolymer. Subsequently, 10kg of the terpolymer was dispersed in 64L of a 0.1mol / L sodium hydroxide solution, and then heated and stirred at 80°C until the system was completely clarified. While keeping the temperature, 36L of a 0.1mol / L lanthanum chloride solution was added, and the reaction was continued with stirring for 30min. The mixture was cooled, allowed to stand, and filtered to obtain a residue. The residue was washed several times with deionized water and then vacuum dried at 50°C for 24h to obtain a lanthanum-modified St-MAH-AN terpolymer.

[0049] Preparation Example 6.2 The preparation method of lanthanum modified St-MAH-AN terpolymer comprises the following steps: 3kg of styrene, 2kg of acrylonitrile, 8kg of maleic anhydride and 30g of dibenzoyl peroxide were mixed and reacted at 70°C for 2h. At this time, the polymerized liquid became viscous and was washed with a 3wt% ethanol solution and dried to obtain a terpolymer. Subsequently, 10kg of the terpolymer was dispersed in 64L of a 0.1mol / L sodium hydroxide solution, and then heated and stirred at 80°C until the system was completely clarified. While keeping the temperature, 72L of a 0.1mol / L lanthanum chloride solution was added, and the reaction was continued with stirring for 30min. The mixture was cooled, allowed to stand, and filtered to obtain a residue, which was washed several times with deionized water and then vacuum dried at 50°C for 24h to obtain a lanthanum-modified St-MAH-AN terpolymer.

[0050] Preparation Example 7.1 The preparation method of lanthanum-modified St-MAH-AN terpolymer is different from that of Preparation Example 6.1 in that the concentration of lanthanum chloride solution remains unchanged and the amount used is 46 L. The rest is the same as Preparation Example 6.1.

[0051] Preparation Example 7.2 The preparation method of lanthanum-modified St-MAH-AN terpolymer is different from that of Preparation Example 6.1 in that the concentration of lanthanum chloride solution remains unchanged and the amount used is 57.6 L. The rest is the same as Preparation Example 6.1.

[0052] Preparation Example 7.3 The preparation method of lanthanum-modified St-MAH-AN terpolymer is different from that of Preparation Example 6.1 in that the concentration of lanthanum chloride solution remains unchanged and the amount used is 64 L. The rest is the same as Preparation Example 6.1.

[0053] Comparative Preparation Example 1 The preparation method of the acrylic copolymer is different from that of Preparation Example 1.1 in that the amount of tert-dodecyl mercaptan used is 25 g, and the rest is the same as Preparation Example 1.1, and an acrylic copolymer with an intrinsic viscosity of 6.11 dL / g is obtained.

[0054] Comparative Preparation Example 2 The preparation method of St-MAH-AN terpolymer comprises the following steps: 6 kg of styrene, 4 kg of acrylonitrile, 16 kg of maleic anhydride and 60 g of dibenzoyl peroxide were mixed and reacted at 70°C for 2 hours. At this time, the polymerized liquid became viscous and was washed with a 3 wt% ethanol solution and dried to obtain a St-MAH-AN terpolymer.

[0055] Example 1.1 A preparation process of a high temperature resistant and low loss radio frequency cable for an intelligent connected vehicle comprises the following steps: S1. Mixing: Stir polyvinyl chloride, heat stabilizer and refractory filler at a speed of 800 r / min for 5 min, then add acrylate copolymer at a speed of 5 kg / min at a speed of 800 r / min, mix at a speed of 1200 r / min for 5 min until there is no powder accumulation on the liquid surface, and finally mix at a speed of 1400 r / min for 25 min to obtain a mixture. The specific amounts of materials are shown in Table 1, wherein the acrylate copolymer is prepared by Preparation Example 1.1, the phosphorus compound modified magnesium aluminum type hydrotalcite is prepared by Preparation Example 4.1, the lanthanum modified St-MAH-AN ternary copolymer is prepared by Preparation Example 6.1, the refractory filler A is mica, and the refractory filler B is antimony trioxide; S2, preparing crude cable; S3. Preparation of high temperature resistant and low loss radio frequency cable: feeding the mixture obtained in step S1 into an extruder, and performing extrusion on the outer layer of the crude cable, the temperatures of zones 1 to 8 of the extruder are 125°C, 140°C, 160°C, 160°C, 170°C, 170°C, 180°C and 180°C respectively, the extrusion current of the extruder is 130A, the screw speed of the extruder is not more than 30r / min, the production speed is 35m / min, to form a sheath layer, and finally obtain a high temperature resistant and low loss radio frequency cable.

[0056] Example 1.2 A preparation process of a high temperature resistant and low loss radio frequency cable for an intelligent connected vehicle comprises the following steps: S1. Mixing: Stir polyvinyl chloride, heat stabilizer and refractory filler at a speed of 1000 r / min for 5 min, then add acrylate copolymer at a speed of 600 r / min at a feeding rate of 5 kg / min, mix at a speed of 1400 r / min for 5 min until there is no powder accumulation on the liquid surface, and finally mix at a speed of 1200 r / min for 25 min to obtain the raw materials for the sheath. The specific amounts of the materials are shown in Table 1, wherein the acrylate copolymer is prepared by Preparation Example 1.2, the phosphorus compound modified magnesium aluminum type hydrotalcite is prepared by Preparation Example 4.2, the lanthanum modified St-MAH-AN ternary copolymer is prepared by Preparation Example 6.2, the refractory filler A is calcium carbonate, and the refractory filler B is magnesium oxide; S2, preparing crude cable; S3. Preparation of high temperature resistant and low loss radio frequency cable: feeding the mixture obtained in step S1 into an extruder, and performing extrusion on the outer layer of the crude cable, the temperatures of zones 1 to 8 of the extruder are 125°C, 140°C, 160°C, 160°C, 170°C, 170°C, 180°C and 180°C respectively, the extrusion current of the extruder is 130A, the screw speed of the extruder is not more than 30r / min, the production speed is 35m / min, to form a sheath layer, and finally obtain a high temperature resistant and low loss radio frequency cable.

[0057] Example 1.3 A preparation process of a high temperature resistant and low loss radio frequency cable for an intelligent connected vehicle comprises the following steps: S1. Mixing: Stir polyvinyl chloride, heat stabilizer and refractory filler at a speed of 800 r / min for 5 min, then add acrylate copolymer at a speed of 5 kg / min at a speed of 800 r / min, mix at a speed of 1200 r / min for 5 min until there is no powder accumulation on the liquid surface, and finally mix at a speed of 1400 r / min for 25 min to obtain the raw materials for the sheath. The specific amounts of the materials are shown in Table 1, wherein the acrylate copolymer is prepared by Preparation Example 1.1, the phosphorus compound modified magnesium aluminum type hydrotalcite is prepared by Preparation Example 4.1, the lanthanum modified St-MAH-AN ternary copolymer is prepared by Preparation Example 6.1, the refractory filler A is mica, and the refractory filler B is antimony trioxide; S2, preparing crude cable; S3. Preparation of high temperature resistant and low loss radio frequency cable: feeding the mixture obtained in step S1 into an extruder, and performing extrusion on the outer layer of the crude cable, the temperatures of zones 1 to 8 of the extruder are 125°C, 140°C, 160°C, 160°C, 170°C, 170°C, 180°C and 180°C respectively, the extrusion current of the extruder is 130A, the screw speed of the extruder is not more than 30r / min, the production speed is 35m / min, to form a sheath layer, and finally obtain a high temperature resistant and low loss radio frequency cable.

[0058] Table 1 Amount of each substance used in step S1 in Examples 1.1-1.2 (kg)

[0059] Example 1.4 A process for preparing a high-temperature resistant and low-loss radio frequency cable for an intelligent connected vehicle, which differs from Example 1.3 in that: in step S1, the amount of the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 1.1 is 12 kg, the amount of zinc borate is 2.4 kg, the amount of the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is 3.6 kg, and the rest is the same as Example 1.3.

[0060] Example 1.5 A preparation process for a high-temperature resistant and low-loss radio frequency cable for an intelligent connected vehicle, which differs from Example 1.3 in that: in step S1, the amount of the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 1.1 is 12.5 kg, the amount of zinc borate is 2.5 kg, the amount of the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is 3 kg, and the rest is the same as Example 1.3.

[0061] Examples 2.1-2.3 A preparation process of a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles, which is different from Example 1.4 in that: in step S1, the acrylic copolymers prepared in Preparation Example 1.1 are replaced by the acrylic copolymers prepared in Preparation Examples 2.1-2.3 respectively, and the rest are the same as Example 1.4.

[0062] Examples 3.1-3.3 A preparation process of a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles, which differs from Example 2.2 in that: in step S1, the acrylic copolymers prepared in Preparation Example 2.2 are replaced by the acrylic copolymers prepared in Preparation Examples 3.1-3.3, respectively, and the rest are the same as Example 2.2.

[0063] Examples 4.1-4.2 A preparation process of a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles, which is different from Example 1.4 in that: in step S1, the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is replaced by the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Examples 4.3-4.4, respectively, and the rest is the same as Example 1.4.

[0064] Examples 5.1-5.3 A preparation process of a high-temperature resistant and low-loss radio frequency cable for intelligent connected vehicles, which is different from Example 1.4 in that: in step S1, the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is replaced by the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Examples 5.1-5.3, respectively, and the rest is the same as Example 1.4.

[0065] Examples 6.1-6.3 A preparation process for a high-temperature resistant and low-loss radio frequency cable for an intelligent connected vehicle, which differs from Example 1.4 in that: in step S1, the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is replaced by the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Examples 7.1-7.3, respectively, and the rest is the same as Example 1.4.

[0066] Comparative Example 1.1 The difference from Example 1.4 is that in step S1, the acrylic copolymer prepared in Preparation Example 1.1 is replaced by dioctyl phthalate, and the rest is the same as Example 1.4.

[0067] Comparative Example 1.2 The difference from Example 1.4 is that in step S1, the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is removed, the amount of zinc borate used is 7.2 kg, the amount of lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is 10.8 kg, and the rest is the same as Example 1.4.

[0068] Comparative Example 1.3 The difference from Example 1.4 is that in step S1, zinc borate is removed, the amount of phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is 13.8 kg, the amount of lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is 4.2 kg, and the rest is the same as Example 1.4.

[0069] Comparative Example 1.4 The difference from Example 1.4 is that in step S1, the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is removed, the amount of zinc borate used is 5 kg, the amount of phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is 15 kg, and the rest is the same as Example 1.4.

[0070] Comparative Example 2.1 The difference from Example 1.4 is that in step S1, the acrylic acid ester copolymer prepared in Preparation Example 1.1 is replaced by the acrylic acid ester copolymer prepared in Comparative Preparation Example 1, and the rest is the same as Example 1.4.

[0071] Comparative Example 2.2 The difference from Example 1.4 is that in step S1, the phosphorus-based compound-modified magnesium-aluminum hydrotalcite prepared in Preparation Example 4.1 is replaced by magnesium-aluminum hydrotalcite, and the rest is the same as Example 1.4.

[0072] Comparative Example 2.3 The difference from Example 1.4 is that in step S1, the lanthanum-modified St-MAH-AN terpolymer prepared in Preparation Example 6.1 is replaced by the St-MAH-AN terpolymer prepared in Comparative Preparation Example 1, and the rest is the same as Example 1.4.

[0073] Performance Testing 1. The cables prepared in the examples and comparative examples were placed in a N2 atmosphere, and the temperature was increased from 25°C to 150°C at a heating rate of 10°C / min. The mass retention rate (%) of each group of cables was recorded in Table 2; 2. The high temperature power supply stability of the cables prepared in the examples and comparative examples was measured with reference to the standard of GB / T 19216.21-2003. The applied voltage was 1000V and the fire supply time was 180min. The highest fire supply temperature (°C) at which no short circuit (2A fuse did not blow) and no conductor melt (indicator light did not go out) was maintained during the test, and was recorded in Table 2. 3. Take off 5g of the sheath layer of the cable prepared in the embodiment and the comparative example, press it into a 3mm thin slice, fix the slice on the wear tester, and scrape it the same number of times under a friction force of 50N. Take off the slice and weigh the mass. The worn mass is used as a parameter for evaluating the wear resistance of the material, and the mass loss rate (%) is recorded in Table 2.

[0074] Table 2 Performance test table

[0075] Data Analysis: As can be seen from Table 2, the high temperature resistant and low loss RF cables for intelligent connected vehicles obtained in Examples 1.1-1.3 have a high temperature mass retention rate of 98.3-98.9% at 150°C, a friction mass loss rate of 1.40-1.41% under a friction force of 50N, and a maximum ignition temperature of 920-935°C, which proves that the present application utilizes various substances within a limited ratio range to give full play to the synergistic effect between the thermal stabilizer and the refractory filler, thereby improving the thermal stability of the sheath layer, and utilizes an acrylic copolymer with a characteristic viscosity of <5.8 dL / g to improve the compatibility between the various substances in the system. The above substances are blended and extruded with polyvinyl chloride to obtain a sheath layer with good thermal stability and mechanical strength, which provides good protection for the cable as a whole.

[0076] The difference between Example 1.4-1.5 and Example 1.3 lies in the weight ratio of phosphorus-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN ternary copolymer in the thermal stabilizer, wherein the cable of Example 1.4 has the highest high-temperature mass retention rate and the highest ignition temperature, and the lowest friction mass loss rate, proving that the specific ratio of the present application can maximize the synergistic effect of each component. The phosphorus-modified magnesium-aluminum hydrotalcite has good flame retardant and heat-resistant properties, can decompose and absorb heat at high temperature, and reduce oxygen concentration; zinc borate further enhances the flame retardant effect, while optimizing the effects of other thermal stabilizers; lanthanum-modified St-MAH-AN ternary copolymer improves the mechanical strength and weather resistance of the material. The composite effect of these components at the optimal ratio significantly improves the overall thermal stability and mechanical properties of the sheath layer, effectively prevents aging, cracking or melting of the insulating layer at high temperature, thereby reducing the probability of safety hazards such as short circuit and leakage, and ensuring the safe and reliable operation of the charging and discharging system.

[0077] The difference between Examples 2.1-2.3 and Example 1.4 is that the characteristic viscosity of the acrylic copolymers used is different. Among them, the cable of Example 2.2 has the highest high-temperature mass retention rate and the highest fire supply temperature, and the lowest friction mass loss rate, which proves that the application controls the amount of tert-dodecyl mercaptan in the process of preparing the acrylic copolymers, so that the characteristic viscosity of the acrylic copolymers is at the most suitable size, and it is more effectively entangled with the molecular chains of polyvinyl chloride, ensuring that the acrylic copolymers, the refractory filler and the thermal stabilizer are all evenly interspersed in the polyvinyl chloride matrix, thereby further improving the compatibility of various substances in the sheath layer and the overall mechanical strength and thermal stability of the sheath layer.

[0078] The difference between Examples 3.1-3.3 and Example 1.4 lies in that the types of monomers in the acrylic ester copolymers used are different, and the high-temperature mass retention rate and the maximum ignition temperature of the cables of Examples 3.1-3.3 are lower than those of Example 1.4, and the friction mass loss rate is also higher than that of Example 1.4, which proves that the use of isobornyl acrylate in the present application can achieve a better thermal stability improvement effect than other acrylic monomers, and its compatibility with the polyvinyl chloride system is also better, thereby improving the overall thermal stability and mechanical stability of the cable.

[0079] The difference between Examples 4.1-4.2 and Example 1.4 is that the proportions of the various substances in the phosphorus compounds in the phosphorus-modified magnesium-aluminum hydrotalcite used are different, and the high-temperature mass retention rate and the maximum ignition temperature of the cables of Examples 4.1-4.2 are lower than those of Example 1.4, which proves that there is a sufficient synergistic effect between the phosphorus compounds of the present application, and only when they are matched in a certain proportion can they achieve an unexpected effect of improving heat resistance.

[0080] The difference between Examples 5.1-5.3 and Example 1.4 is that the phosphorus compounds in the phosphorus-modified magnesium-aluminum hydrotalcite used are different, and the high-temperature mass retention rate and the maximum ignition temperature of the cables of Examples 5.1-5.3 are lower than those of Example 1.4, which proves that there is sufficient synergistic effect between the phosphorus compounds of the present application, and when the cable is heated, a stable protective film can be formed in the sheath layer system, effectively inhibiting the decomposition and combustion of the sheath layer, reducing smoke generation, and improving the overall flame retardant properties and heat stability of the sheath layer.

[0081] The difference between Examples 6.1-6.3 and Example 1.4 is that different lanthanum-modified St-MAH-AN terpolymers are used. Among them, the cable of Example 6.2 has the highest high-temperature mass retention rate and maximum fire supply temperature, and the lowest friction mass loss rate, which proves that the present application optimizes the lanthanum doping rate to the greatest extent without incurring additional costs by strictly controlling the weight ratio of the terpolymer to lanthanum ions, thereby increasing the heat resistance of the sheath layer to the highest level, effectively preventing aging, cracking or melting of the sheath layer caused by high temperature, reducing the risk of short circuit and leakage, and ensuring the safe and reliable operation of the cable.

[0082] The difference between Comparative Example 1.1 and Example 1.4 is that the acrylic copolymer prepared in Preparation Example 1.1 is replaced by dioctyl phthalate. The data show that the high-temperature mass retention rate and the maximum ignition temperature of the cable of Comparative Example 1.1 are lower than those of Example 1.4, and the friction mass loss rate is also higher than that of Example 1.4, which proves that the acrylic copolymer of the present application improves the compatibility of various substances in the system, so that the compatibility inside the sheath layer is significantly optimized, thereby not only improving the thermal stability of the sheath layer, but also improving the mechanical stability of the sheath layer.

[0083] The difference between Comparative Examples 1.2-1.4 and Example 1.4 is that the phosphorus-based compound-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN ternary copolymer in the thermal stabilizer are respectively removed. The data show that the high-temperature quality retention rate and the maximum ignition temperature of the cables of Comparative Examples 1.2-1.4 are lower than those of Example 1.4, proving that the phosphorus-based compound-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN ternary copolymer of the present application can fully exert a good synergistic effect after blending, greatly improving the thermal stability of the sheath layer.

[0084] The difference between Comparative Example 2.1 and Example 1.4 is that the characteristic viscosity of the acrylic copolymer is different. The data show that the high-temperature mass retention rate and the maximum ignition temperature of the cable of Comparative Example 2.1 are lower than those of Example 1.4, and the friction mass loss rate is also much higher than that of Example 1.4, which proves that the acrylic copolymer of the present application improves the compatibility of various substances in the system, and strictly controls the characteristic viscosity of the acrylic copolymer to be less than 5.8 dL / g, so that the compatibility inside the sheath layer is significantly optimized, thereby not only improving the thermal stability of the sheath layer, but also improving the mechanical stability of the sheath layer.

[0085] The difference between Comparative Examples 2.2-2.3 and Example 1.4 is that the phosphorus-modified magnesium-aluminum hydrotalcite and the lanthanum-modified St-MAH-AN ternary copolymer are replaced respectively. The data show that the high-temperature quality retention rate and the maximum ignition temperature of the cables of Comparative Examples 2.2-2.3 are lower than those of Example 1.4, proving that the phosphorus-modified magnesium-aluminum hydrotalcite and the lanthanum-modified St-MAH-AN ternary copolymer of the present application have extremely high thermal stability. At the same time, compared with the unmodified substances themselves, the synergistic effect between the two and zinc borate is also better.

[0086] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high temperature resistant and low loss radio frequency cable for intelligent networked vehicles, comprising a twisted wire core, a wrapping layer, a shielding layer and a sheath layer sequentially coated on the outer side of the twisted wire core, characterized in that: The raw materials used for the sheath layer include the following components by weight: 100 parts of polyvinyl chloride; 30-35 parts of acrylic copolymer; 15-20 parts of heat stabilizer and 15-20 parts of refractory filler; The intrinsic viscosity of the acrylic copolymer is less than 5.8 dL / g, and the thermal stabilizer includes a phosphorus compound-modified magnesium-aluminum hydrotalcite, zinc borate and lanthanum-modified St-MAH-AN terpolymer in a weight ratio of 25:5:(5-8).

2. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 1, characterized in that: The raw materials used for the sheath layer include the following components by weight: 100 parts of polyvinyl chloride; 32 parts of acrylic copolymer; 18 parts of heat stabilizer and 18 parts of refractory filler.

3. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 2, characterized in that: The thermal stabilizer comprises a weight ratio of 25:5: 7.5 phosphorus compound modified magnesium aluminum type hydrotalcite, zinc borate and lanthanum modified St-MAH-AN terpolymer.

4. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 1, characterized in that: The acrylic acid ester copolymer is prepared by the following method: Methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan in a weight ratio of 120:10:(0.5-2.0) are mixed and dispersed in water containing initiator a and emulsifier, stirred for reaction, demulsified and dried to obtain an acrylic copolymer with an intrinsic viscosity of less than 5.8 dL / g.

5. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 4, characterized in that: The weight ratio of the methyl methacrylate, isobornyl acrylate and tert-dodecyl mercaptan is 120:10:1.

3.

6. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 1, characterized in that: The phosphorus compound in the phosphorus compound-modified magnesium-aluminum hydrotalcite includes ammonium polyphosphate, resorcinol bis(diphenyl phosphate) and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in a weight ratio of 1:(0.5-1):(1-1.5).

7. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 1, characterized in that: The lanthanum-modified St-MAH-AN terpolymer is prepared by the following method: Styrene, acrylonitrile, maleic anhydride and initiator b are blended, heated to react, washed, and dried to obtain a terpolymer. The terpolymer is then dispersed in an alkaline solution, heated and stirred until the system is completely clarified and then kept warm. A lanthanum chloride solution is then added to ensure that the weight ratio of the terpolymer to lanthanum ions in the system is 10:(0.5-1). The reaction is stirred, cooled, allowed to stand, filtered to obtain a filter residue, washed, and dried to obtain a lanthanum-modified St-MAH-AN terpolymer.

8. The high temperature resistant and low loss radio frequency cable for intelligent networked vehicles according to claim 7, characterized in that: After adding the lanthanum chloride solution, the weight ratio of the terpolymer to the lanthanum ions in the system is 10:0.

8.

9. A process for preparing a high temperature resistant and low loss radio frequency cable for an intelligent networked vehicle according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing: the polyvinyl chloride, heat stabilizer and refractory filler are stirred at a speed of 800-1000 r / min, and then the acrylic copolymer is added at a speed of 600-800 r / min, and after the addition is completed, the material is mixed at a speed of 1200-1400 r / min until there is no powder accumulation on the liquid surface, and then the material is further mixed at a speed of 1200-1400 r / min to obtain a mixture; S2. Preparing a crude cable: coating an insulating layer on the surface of a conductor to obtain a twisted wire core, and then sequentially coating a sheath layer and a shielding layer on the outer side of the twisted wire core to obtain a crude cable; S3. Preparation of high temperature resistant and low loss radio frequency cable: Extruding the mixture obtained in step S1 onto the outside of the crude cable obtained in step S2 to form a sheath layer, thereby obtaining a high temperature resistant and low loss radio frequency cable.

Citation Information

Patent Citations

  • Inorganic combustion inhibitor of polyphosphoric acid radical column supported hydrotalcite and method for preparing same

    CN101284994A

  • Large-particle-size acrylate impact modifier for polyvinyl chloride and preparation method thereof

    CN104231151A

  • Lanthanum ionomer, preparation method thereof and polyvinyl chloride blend

    CN107417817A

  • Network cable for monitoring equipment and preparation process thereof

    CN116884698A

  • PVC (polyvinyl chloride) high-temperature-resistant vehicle cable material as well as preparation and application thereof

    CN117186570A